2008
DOI: 10.1210/jc.2008-0801
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the Oral Glucose Tolerance Test in Overweight Children

Abstract: Our results show poor reproducibility of the OGTT in obese youth, in particular for the 2-h plasma glucose. Obese youth who have discordant OGTT results are more insulin resistant with higher risk of developing type 2 diabetes mellitus, as evidenced by a lower GDI. The implications of this remain to be determined in clinical and research settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
131
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 24 publications
13
131
1
3
Order By: Relevance
“…Of note, however, is that the OGTT-derived indices of insulin resistance (WBISI) and secretion (IGI) employed in the current study were validated by our group and were found to correlate relatively well with clamp-derived insulin sensitivity and secretion measures in obese children and adolescents [15,19]. Reproducibility of the OGTT as a tool to detect glucose regulation is known to be poor, particularly for 2 h plasma glucose [20]. Such variability of the OGTT is not surprising, given that basal and postprandial measures of glucose and insulin are highly variable, reflecting changes in nutrition and physical activity, and are influenced by seasonal and diurnal factors.…”
Section: Discussionmentioning
confidence: 67%
“…Of note, however, is that the OGTT-derived indices of insulin resistance (WBISI) and secretion (IGI) employed in the current study were validated by our group and were found to correlate relatively well with clamp-derived insulin sensitivity and secretion measures in obese children and adolescents [15,19]. Reproducibility of the OGTT as a tool to detect glucose regulation is known to be poor, particularly for 2 h plasma glucose [20]. Such variability of the OGTT is not surprising, given that basal and postprandial measures of glucose and insulin are highly variable, reflecting changes in nutrition and physical activity, and are influenced by seasonal and diurnal factors.…”
Section: Discussionmentioning
confidence: 67%
“…Since fasting blood glucose failed to diagnose diabetes mellitus in one fourth of children with type 2 diabetes mellitus in the European cohort [3] , oGTT seems to be a better screening tool even if fasting glucose is preferred because of its lower costs and greater convenience. However, the low reproducibility of an oGTT has to be kept in mind [48] . Using the criteria (1) type 2 diabetes mellitus in the first or second degree relatives, (2) onset of puberty, and (3) extreme obesity allows to identify the great majority of overweight European children, which should be screened by oGTT, when two of this three criteria are fulfilled [49] .…”
Section: Screening For Type 2 Diabetes Mel-litus In Children and Adolmentioning
confidence: 99%
“…TRT reliability was evaluated by Libman et al 176 in a study that compared measurement of glucose via fasting and 2-hour samples in 60 overweight/obese adolescents. Results indicated that fasting glucose (r = 0.73) had higher reliability than 2-hour glucose (r = 0.37) testing.…”
Section: Onlymentioning
confidence: 99%